Calculation of the Real Corneal Refractive Power after Photorefractive Keratectomy Using Pentacam, When Only the Preoperative Refractive Error is Known. (1st April 2020) - De Bernardo, Maddalena; Borrelli, Maria; Imparato, Roberto; Rosa, Nicola
Abstract : Purpose . To check if a regression formula, IOLMaster-derived, to calculate the real corneal power after photorefractive keratectomy (PRK), can give reliable results utilizing the Pentacam. Methods . Pre- and postoperative IOLMaster, Km, and Pentacam K readings were measured. Patients who had myopic PRK were divided into two groups: the first group (108 eyes) was utilized to check which of the preop Pentacam K readings (P-Kpre) better fitted with the preop IOLMaster measurements; in the second group (120 eyes), the real K (Kr), obtained adding the effective treatment to the P-Kpre, were compared with the K readings calculated with the IOLMaster-derived formula (Kc). Moreover, an attempt to find a different formula utilizing the P-Kpre was made. Results . In group 1, the best correlation was found between IOLMaster Km and Pentacam equivalent K readings (r2 0.9519). In group 2, the comparison between Kr and Pentacam postop Km showed 69 eyes (57%) with differences >0.5 D and 38 eyes (31%) with differences >1 D, (P < 0.001 ). The comparison between Kr and Kc showed 55 eyes (45%) with differences >0.5 D and 22 eyes (18%) with differences >1 D, (P < 0.001 ). Moreover, a regression formula K = EKR − [ETcp + (0.8114 ∗ ETcp − 0.2031)] was obtained in order to calculate the K readings to be used with the Pentacam in the IOL power calculation in case the effective treatment is known. Conclusions . K calculated with the new formula could be used in patients that underwent refractive corneal surgery in case a Pentacam device is used, pending further studies conducted in clinical practice to establish its accuracy and effectiveness. This study further proves that data obtained from different machines cannot be used interchangeably.